STUDI STRATEGI PENANGANAN PINJAMAN PEMBIAYAAN KSP KSPPS DI ERA PANDEMI COVID-19 DI DAERAH ISTIMEWA YOGYAKARTA - Suhartono Suhartono; Achmad Tjahjono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The objectives of this study are: Mapping short-term and long-term strategies for Koperasi Simpan Pinjam (KSP) and or Koperasi Simpan Pinjam Syariah (KSPPS) in handling loans in the Covid-19 pandemic era and mapping KSP/KSPPS strategies in handling non-performing loans. in the era of the covid-19 pandemic. This research is a qualitative descriptive study. The data collected is in the form of data on the handling of loans/financing carried out by KSP and KSPPS. Data collection methods used are documentation, questionnaires and interviews. Documents in the form of RAT reports for 2020 and 2021, questionnaires and interviews were conducted online using google forms and chat, with the research subjects being KSP and KSPPS managers throughout DIY. The results of the study indicate that there are 5 (five) short-term strategies and 4 (four) long-term strategies that need to be implemented, while there are 3 (three) strategies that need to be implemented in handling non-performing loans. The limitation of this study is that in digging up data, it only uses Google Forms which are distributed to several social media groups as well as individual KSP/KSPPS managers and also interviews with online systems so that the sample cannot be large. Meanwhile, recommendations that can be given for future research are that more research samples can be added, and the research area can be expanded.